Dynamic change of microbial community structure of activated sludge influenced by oxytetracycline in wastewater - TANG Lu; NIU Chengzhen; LYU Zhenmei (浙江大学学报. 农业与生命科学版, 2013)
Oxytetracycline (OTC), a broad-spectrum antibiotic, has been widely used in defense against infectious gram-positive and gram-negative bacteria that are pathogenic to livestock. As a result, OTC can be detected in various effluents, such as livestock wastewater, municipal sewage, and hospital wastewater, as well as their receiving environments. Activated sludge has played an important role in wastewater treatment for nearly one hundred years. However, the pervasiveness of OTC in modern waste streams reduces the viability of microorganisms in activated sludge which are inhibited by OTC. This study was carried out to investigate the interaction between wastewater treatment efficiency and the activity of microbial communities in activated sludge under long-term exposure to OTC.Sequencing batch reactors (SBRs) treating wastewater containing concentrations of 0, 0.1, 5, 20, 60 mg/L OTC were established and studied for 88 days, respectively. All reactors were discharged of effluent every two days and then supplied with a new batch of artificial wastewater. The performance of each reactor was determined by measuring pH, total nitrogen (TN) removal rate and concentration of chemical oxygen demand (COD) in the effluent. Denaturing gradient gel electrophoresis (DGGE), targeting the V6 V7 region of 16S rRNA gene, was applied to analyze the variation in bacterial community structure in the activated sludge as influenced by different concentrations of OTC. Additionally, scanning electron microscopy (SEM) was employed to observe the morphology of activated sludge.Results showed that the wastewater treatment efficiency of activated sludge was inhibited by OTC, especially when OTC concentration was above 20 mg/L. However, treatment efficiency of activated sludge containing OTC would tend to recover in the course of extended operation time. According to SEM results, richer morphological diversity was observed in R1 (control group without OTC) than in treatment groups (with varying concentrations of OTC) during the course of operation. Filamentous bacteria was only found in R1, and the amount of rod-shaped bacteria decreased while coccus bacteria became more dominant in treatment groups, indicating that rod-shaped bacteria was more sensitive to OTC than coccus bacteria. After operation of SBRs for 88 days, larger round-shaped microorganisms appeared both in R1 and in treatment groups with OTC lower than 60 mg/L. We confer that the microorganisms may be Saccharomycetes, which increased as the concentrations of OTC in the treatment groups increased, except for the group with 20 mg/L OTC. DGGE results indicated that the diversity of microbial community structure was dynamically changed during the procedure and was influenced by the different concentrations of OTC. Compared with R1, the diversity of treatment groups had declined after 88 days, especially for the reactor with 60 mg/L OTC. Sequencing analysis showed that Proteobacteria and Bacteroidetes were the most abundant phyla in all treatment groups and in R1. Different genera belonging to these phyla displayed different resistances to OTC, however, so that the extent to which wastewater treatment efficiency recovered during the course of reactor operation was distinguished by the predominance of unique microbial populations in the treatment groups.It can be concluded that the microbial community structure and wastewater treatment efficiency of activated sludge are influenced by different concentrations of OTC. The higher the concentration of OTC that is added to treatment groups, the lower the treatment efficiency is. Accumulation of untreated OTC in the low concentration OTC treatment groups may have resulted in an effect of increasing inhibition; however, the microbial community structure varies dynamically and thus the more adaptive species emerges. The emergence of such species may lead to the recovery of wastewater treatment efficiency.